National health registries in professional German football: development and first results from the men`s and women`s 1st and 2nd Bundesliga - Huber, L.; Szymski, D.; Krutsch, W.; Weber, J.; Huppertz, G.; Zeman, F.; Koller, M.; Pietzonka, M.; Klein, C.; Nagel, A.; Alt, V. (BMJ Open Sport & Exercise Medicine, 2026)
Objectives Long-term, nationwide data on injuries and illnesses in professional football, particularly in women, remain limited. This study aimed to describe injury and illness epidemiology in German professional male and female football using prospective registry data, with a focus on incidence, distribution, and return-to-play times and on sex-specific differences.